Role of intracellular complement activation in kidney fibrosis. (27th February 2021) - Portilla, Didier; Xavier, Sandhya
Abstract : Increased expression of complement C1r, C1s and C3 in kidney cells plays an important role in the pathogenesis of kidney fibrosis. Our studies suggest that activation of complement in kidney cells with increased generation of C3 and its fragments occurs by activation of classical and alternative pathways. Single nuclei RNA sequencing studies in kidney tissue from unilateral ureteral obstruction mice show that increased synthesis of complement C3 and C5 occurs primarily in renal tubular epithelial cells (proximal and distal), while increased expression of complement receptors C3ar1 and C5ar1 occurs in interstitial cells including immune cells like monocytes/macrophages suggesting compartmentalization of complement components during kidney injury. Although global deletion of C3 and macrophage ablation prevent inflammation and reduced kidney tissue scarring, the development of mice with cell‐specific deletion of complement components and their regulators could bring further insights into the mechanisms by which intracellular complement activation leads to fibrosis and progressive kidney disease. Linked Articles: This article is part of a themed issue on Canonical and non‐canonical functions of the complement system in health and disease. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.14/issuetoc